Lifespan Estimation of Galvanized Steel and Stainless Steel Pipe - Mohammad Danil Arifin; Moch Ricky Dariansyah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
This research presents a comparative study focused on estimating the lifespan of galvanized steel pipes and stainless steel pipes within the context of a ballast system. Ballast systems play a crucial role in maintaining the stability and trim of vessels, making the longevity of the associated piping materials essential for maritime operations. This research aims to provide insights into the corrosion behavior and overall durability of galvanized steel and stainless steel pipes employed in ballast systems. The investigation involves an in-depth analysis of corrosion mechanisms specific to both galvanized steel and stainless steel pipes in the corrosive marine environment. The influence of factors such as salinity, and immersion time is examined. By understanding the distinct corrosion behavior of galvanized steel and stainless steel pipes, maritime industry stakeholders can make informed decisions regarding material selection, maintenance schedules, and potential retrofitting options. Ultimately, the insights gained from this study contribute to the sustainability and operational efficiency of maritime transport by enabling the optimization of ballast system infrastructure. As regulations and environmental considerations evolve, a comprehensive understanding of the lifespan estimation of galvanized steel and stainless steel pipes aids in mitigating potential failures, reducing downtime, and ensuring the safety and reliability of vessel operations. It is shown that the lifespan of stainless steel is longer than that of galvanized pipe.